Sustainable Cities in Developing Countries theory and practice at the millennium - Pugh, Cedric (London Earthscan, 2000)
Sustainable Cities in Developing Countries creates new paths for the understanding of sustainable urban development. It presents original knowledge, perspectives and examples on the sustainability of cities,grounding its analysis in the dialect between their economic,social,political and enviromental realities. Wide-ranging contributions from world-renowned experts are brought together in a comprehensive and multi-disciplinary review of the major issues, including legal mechanisms, health, economics and the environment, and application of Local Agenda 21 in cities. Tracing the evolution of theory in relation to urban growth and development, it provides guidance for moving towards sustainable urban environments and descriptions of the efforts made by several cities in this respect. Practioners and academics alike will find this book of unique relevance in its rigorous examination of the unfinished agenda relating to urban environmental degradation and in its elaboration of principles of best practice.
Includes bibliographical references and index
Keywords: Sustainable Development, City planning --Developing countries Urban ecology (Sociology) --Developing countries